THE NEED TO TAKE INTO ACCOUNT QUALITY INDICATORS WHEN ASSESSING THE LEVEL OF PUBLIC TRANSPORTATION PROVIDED TO THE POPULATION (Universal International Scientific Journal, 2026)
The assessment of the level of public transport provision is often carried out based on the number of routes, coverage area, passenger flow and density of the transport network. However, in modern conditions, quantitative indicators alone are not enough to realistically assess the effectiveness of the public transport system. This article scientifically substantiates the need to take into account factors related to the quality of service when using public transport - the technical condition and year of manufacture of buses, environmental safety, amenities for people with disabilities, Internet (Wi-Fi) provision, heating and cooling systems, electronic payment options - when assessing the level of provision. Comprehensive consideration of these factors is proposed as an important direction in determining the real value of transport services for the user.
Keywords: new buses; environmental friendliness; accessibility for people with disabilities